Implementation of XML based Digital Signature - Rosalina Rosalina (President University, 2016)
With the development of information technology, computer has played more and more important role in many regions and human’s life. The number of computer and network users is increasing minutes by minutes which make this global network and its information expanding rapidly day by day. Meanwhile, the modern computerized information system has been developed rapidly and implemented in many regions, such as education regions, enterprise and provides an electronic means to access information and data. As the fast development of computerized system, the W3C group has developed a flexible language named XML. The W3C has deemed the Extensible Markup Language (XML) will form the important basis for the information interchange and accessing in the field of computer network. It will make the electronic exchange of documents and other exchangeable information much easier, convenient and less expensive. At the same time, the security requirement (e.g. integrity, authenticity of the information and/or data and/or signer authentication) of accessing and exchanging information and data in a modern computerized information system has increased rapidly, and now, as the development of XML function, a new efficient security technology is provided which is named XML digital signature (XMLDsig). The XML digital signature provides a more flexible secured technology to keep the integrity and authenticity of data and/or information.This paper aim to embed and implement XML based digital signatures to an existing Student Query System model in order to achieve the user authentication and integrity of accessing data and/or information from the system.